Effects of BEIIb-Deficiency on the Cluster Structure of Amylopectin and the Internal Structure of Starch Granules in Endosperm and Culm of Japonica-Type Rice - Nakamura, Yasunori; Ono, Masami; Hatta, Tamao; Kainuma, Keiji; Yashiro, Kazuki; Matsuba, Go; Matsubara, Akira; Miyazato, Akio; Mizutani, Goro (Frontiers in Plant Science, 2020)
It is known that one of starch branching enzyme (BE) isoforms, BEIIb, plays a specific role not only in the synthesis of distinct amylopectin cluster structure, but also in the formation of the internal structure of starch granules in rice endosperm because in its absence the starch crystalline polymorph changes to the B-type from the typical A-type found in the wild-type cereal endosperm starch granules. In the present study, to examine the contribution of BEIIb to the amylopectin cluster structure, the chain-length distributions of amylopectin and its phosphorylase-limit dextrins (Φ-LD) from endosperm and culm of a null be2b mutant called amylose-extender (ae) mutant line, EM10, were compared with those of its wild-type (WT) cultivar, Kinmaze, of japonica rice. The results strongly suggest that BEIIb specifically formed new short chains whose branch points were localized in the basal part of the crystalline lamellae and presumably in the intermediate between the crystalline and amorphous lamellae of amylopectin clusters in the WT endosperm, whereas in its absence branch points which were mainly formed by BEI were only located in the amorphous lamellae of amylopectin. These differences in the cluster structure of amylopectin between Kinmaze and EM10 endosperm were considered to be responsible for the differences in the A-type and B-type crystalline structures of starch granules between Kinmaze and EM10, respectively. The changes in internal structure of starch granules caused by BEIIb were analyzed by wide angle X-ray diffraction, small-angle X-ray scattering, solid state 13C NMR, and optical sum frequency generation spectroscopy. It was noted that the size the amylopectin cluster in ae endosperm (approximately 8.24 nm) was significantly smaller than that in WT endosperm (approximately 8.81 nm). Based on the present results, we proposed a model for the cluster structure of amylopectin in WT and ae mutant of rice endosperm. We also hypothesized the role of BEIIa in amylopectin biosynthesis in culm where BEIIb was not expressed and instead BEIIa was the major BE component in WT of rice.